(untitled) (Studia theodisca, 2019)
In the last of the Pindar-Fragments, a set of nine pieces translated by Friedrich Hölderlin around 1803-1805, the myth of the Centaurs as the symbol for violence and transgression is made to disintegrate and is replaced by an autonomous narrative depicting the birth of culture and civilization. In Hölderlin’s commentary, “the concept of the Centaurs” is said to correspond to the “spirit of a river”, upon which the text seeks to summon up the “image” underlying that same concept. This dynamics of concept and image leads one to fully reconsider the interplay between translation and interpretation.